Violence against women: Advances and throwbacks in the aim of ODS N. º 5 in the peruvian context - Acevedo Rojas, Elba Sissi (2023)
Violence against women is based on a predominantly patriarchal structure where one gender has established itself as the dominant other, which submits the other to its will and has the endorsement of a society lacking respect for human rights. In addition, the timid or non-existent insertion of policies with a gender perspective. Various investigations make visible the high numbers of physical, sexual, psychological, and economic violence to which women and girls are subjected worldwide. In Latin America and the Caribbean, Peru is 38% above the world average for violence and ranked 83 out of 170 countries in equality. The article explains the defects are the characteristics of violence and its manifestations, as well as how a victim ceases to be a victim to become a survivor. The country has made great progress at the regulatory level regarding the prevention and punishment of gender violence, but a great setback in the implementation of policies with a gender perspective at all levels. This essay is exploratory, descriptive, and its purpose is to understand the advances in the reduction of violence against women in Peru.